Penafian al-Qur’an atas Human Trafficking: Aplikasi Teori Ma‘nā-cum-Maghzā Pada QS. an-Nūr [24]: 33 - Khoirul Umami; Muhammad Naufal Hakim (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2021)
As a problematic issue, human trafficking emerges and transforms to the new various forms in contemporary days. Islam rejects the practice of slavery as demonstrated clearly in Qs. al-Nūr [24]: 33. In interpreting the verse, however, the classical and contemporary commentators are mostly concerned only with legal issues within the text. This article, therefore, aims to re-reading the Qur’an by exploring the significance (al-maghzā) of the Qs. al-Nūr [24]: 33, and examining the implication of its meaning on the discourse of human trafficking. This article employs the critical-analytic method and the ma‘nā-cum-maghzā approach. This study argues that the significance (al-maghzā) of Qs. al-Nūr [24]: 33 is on humanization, namely a message to preserve the human dignity, and to prevent any action that leads to the oppression of human rights. The implication of this meaning is that human trafficking in its various forms is an act that is prohibited by Islam.